A two-component nonphotochemical fluorescence quenching in eustigmatophyte algae - Bína, David; Bouda, Karel; Litvín, Radek (Photosynthesis research, 2017)
Eustigmatophyte algae represent an interesting model system for the study of the regulation of the excitation energy flow due to their use of violaxanthin both as a major light-harvesting pigment and as the basis of xanthophyll cycle. Fluorescence induction kinetics was studied in an oleaginous marine alga Nannochloropsis oceanica. Nonphotochemical fluorescence quenching was analyzed in detail with respect to the state of the cellular xanthophyll pool. Two components of nonphotochemical fluorescence quenching (NPQ), both dependent on the presence of zeaxanthin, were clearly resolved, denoted as slow and fast NPQ based on kinetics of their formation. The slow component was shown to be in direct proportion to the amount of zeaxanthin, while the fast NPQ component was transiently induced in the presence of membrane potential on subsecond timescales. The applicability of these observations to other eustigmatophyte species is demonstrated by measurements of other representatives of this algal group, both marine and freshwater.
Keywords: Seaweed; Photosynthesis; Fluorescence; mořské řasy; Xanthophyll cycle; Nonphotochemical quenching; Eustigmatophyceae; fotosyntéza; fluorescence; Chl a fluorescence; Nannochloropsis